PHARMACOGNOSTICAL EVALUATION OF DIFFERENT MARKET SAMPLES OF VIDARIKAND (PUERARIA TUBEROSA DC) IN INDIA (AYUSHDHARA, 2019)
The demand for natural products derived from medicinal plant is increasing in national and international market. Over 86% of raw material required for traditional medicines/herbal medicines used to be collected from wild resources. With the increase in demand of medicinal plants for the commercial herbal medicine sector led to the indiscriminate and unscientific collection without any consideration for the quality of the material collected. Therefore, it has created problem like deforestation, so some plants species have been near to endangered such as Kutki, Jatamansi, Ativisha etc. Vidarikand (Pueraria tuberosa DC) is a drug of high demands. Because of its increasing demand in the pharmaceutical industry, the availability of authentic drug is decreased. This decline in authenticity is due to substitutes or sub standard materials and adulterants. Objective: The main objective of present study is to evaluate the quality of the genuine/official Vidarikand and its commercial sample and to find out whether the genuine/official drug is available in the market or not. Methods: The genuine/official Vidarikand and its three different markets sample in India which are Lucknow, Delhi and Mumbai. Pharmacognostical and phytochemical analysis of official drug and three different market samples have been compared to the standards given in Ayurvedic pharmacopoeia. This research work was conducted in laboratory of State Ayurvedic College, Lucknow and CSIR-NBRI, Lucknow. Observation and Results: As per Pharmacognostical and phytochemical parameters official drug of Vidarikand and its market samples variations were found. Conclusion: In view of pharma-cognostical and phytochemical analysis, the sample of Lucknow and Delhi market were not similar to genuine/official sample, they were totally replaced with other drug and the sample of Mumbai was mixer of two different drugs one was Vidarikand and second was other adulterated drug.